Análises das despesas com pessoal dos municípios da região metropolitana de Natal (2016-2020) - Duarte, Lídia Vitória da Silva (2022)
The public budget is used as a public finance management tool, in which it identifies the origin of the collected revenues and where these resources will be spent. Personnel expenses occupy a large share of current expenditures and, as it affects public expenditures so much, this was one of the reasons for the creation of limits on personnel expenses. This investigation aims to analyze the situation of personnel expenses in the municipalities of the Metropolitan Region of Natal, from 2016 to 2020, in relation to the limits imposed by the Fiscal Responsibility Law (net current revenue). To achieve the objective, the data were extracted from the Fiscal Management Report (RGF) of the last four months and the Summarized Budget Execution Report (RREO) of the last two months of the year, released on the electronic portal of the Secretaria do Tesouro Nacional (STN). The results revealed that in the period from 2016 to 2020, the limits set in the Fiscal Responsibility Law, of personnel expenses in relation to the Net Current Revenue, were not obeyed by almost all the municipalities of Grande Natal, with the exception of Bom Jesus, which was below the alert threshold in all years. It was also identified that, with the exception of São Gonçalo do Amarante (in 2019 and 2020), Bom Jesus (in 2020), Ielmo Marinho (2018), Maxaranguape (2018) and Parnamirim (2020), all municipalities allocated more than 50% from its current income to the cost of personnel expenses. This research contributes to the social control of the population from the propagation of the importance of controlling payroll expenditures and transparency on the real situation of these expenditures in the last five years.